Comprehensive Analysis of Silencing Mutants Reveals Complex Regulation of the Arabidopsis Methylome - Stroud, Hume; Greenberg, Maxim V.C.; Feng, Suhua; Bernatavichute, Yana V.; Jacobsen, Steven E. (Cell, 2013)
Cytosine methylation is involved in various biological processes such as silencing of transposable elements (TEs) and imprinting. Multiple pathways regulate DNA methylation in different sequence contexts, but the factors that regulate DNA methylation at a given site in the genome largely remain unknown. Here we have surveyed the methylomes of a comprehensive list of 86 Arabidopsis gene silencing mutants by generating single-nucleotide resolution maps of DNA methylation. We find that DNA methylation is site specifically regulated by different factors. Furthermore, we have identified additional regulators of DNA methylation. These data and analyses will serve as a comprehensive community resource for further understanding the control of DNA methylation patterning. [Display omitted] ► Genome-wide single-nucleotide resolution methylation maps in 86 silencing mutants ► Complex interplays between different DNA methylation pathways ► Identification of novel regulators of DNA methylation A genome-wide study of DNA methylation in a comprehensive list of Arabidopsis mutants implicated in gene silencing and histone modification reveals that different pathways regulate DNA methylation site specifically, and the study uncovers new factors that regulate DNA methylation.